Synthesis and structure of thiourea derivatives of functionally substituted pyridines - Nurkenov, O.A.; Fazylov, S.D.; Seilkhanov, T.M.; Nurmaganbetov, Zh.; Gazaliev, A.M.; Karipova, G.Zh. (KU Publ., 2021)
The article presents data on the synthesis and study of the structure of thiourea derivatives of functionally substituted pyridines. New thiourea derivatives containing a pharmacologically active pyridine moiety in their structure were obtained. As the starting synton, 2-amino-5-bromopyridine, 2-amino-3-hydroxypyridine and 2-aminomethylpyridine were selected. It was shown that the interaction of 2-amino-5-bromopyridine, 2-amino-3-hydroxypyridine and 2-aminomethylpyridine with ethyl and phenylisothiocyanates in ethanol leads to the formation of the corresponding pyridine-containing thioureas. The synthesis of the initial isothiocyanates was carriedout in situ from the corresponding acidic chlorides (benzoyl chloride and p-brombenzoyl chloride) by heating them with potassium thiocyanate in acetone. The structure of the synthesized compounds was studied by 1H and 13C NMR spectroscopy, as well as by the data of two-dimensional spectra of COSY (1H-1H) and HMQC (1H-13C). The values of chemical shifts, multiplicity, and integrated intensity of 1H and 13C signals in one-dimensional NMR spectra were determined. Using spectra in the formats COSY (1Н-1Н) and HMQC (1Н-13С), homo- and heteronuclear interactions were established, confirming the structure of the studied compounds.
Функционалдық-орынбасылған пиридиндердің тиомочевинді туындыларының синтезі және құрылысы
Синтез и строение тиомочевинных производных функционально-замещенных пиридинов
Keywords: ethylisothiocyanates; phenylisothiocyanates; 2-amino-5-bromopyridine; 2-amino-3-hydroxypyridine; 2-aminomethylpyridine; thioureas; 2-aminopyridine; 1H and 13C NMR spectra